DEVELOPMENT OF NUMERICAL PLATFORM FOR AIRCRAFT SYSTEMS SIMULATION - Rianto A Sasongko; Yorgi A. Ndaomanu; Yazdi I. Jenie; M. Luthfi I. Nurhakin; M. Rafi Hadytama; Yusuf K Asalani (INSIST, 2017)
This paper discusses the development of a numerical simulation platform that can be used for representing the principal works of aircraft systems. The platform consists of some parts each of which is intended to replicate the operation of a system implemented in a modern aircraft, such as hydraulic line, electrical system, landing gear system, control system, etc. The platform is intended to be a tool for modeling and analyzing the operation and performance of certain systems configuration. To some extend the platform can be viewed as a virtual Iron Bird System. Iron Bird is a term representing a platform for simulating the works of aircraft systems using real components, which is very important for aircraft system development. At this stage, the numerical platform will only involve some sub-systems, namely main hydraulic line, control surface actuation, landing gear, and control system. These sub-systems are chosen to be the basis for further development where other sub-systems will be added and integrated to the platform.Keywords—Aircraft System, Numerical Simulation, System Analysis